Transcriptomes of Populus lines modified in Pectin methylesterase expression reveal activation of oxidative stress signaling pathways - Öhman, David (2006)
Pectin methylesterases (PMEs) catalyze the demethylesterification of cell wall polygalacturonans, and this is thought to play important roles in cell wall extensibility and intercellular adhesion. In addition, PMEs influence many physiological processes, such as stem elongation, root development, fertilization, fruit softening, and xylogenesis. This study focuses on establishing gene expression profiles for transgenic poplar (Populus tremula L. x P. tremuloides Michx.) lines, over-expressed (PME 2B and PME 7) and suppressed (PME 5 and PME 6N), in the expression of PME1. Employment of a transcriptomic approach; spotted poplar cDNA 25 K microarrays, allowed for a simultaneous analysis of about 17,000 genes, gaining insight into effects on plant cell metabolism. A concluding remark of the outcome of the microarray experiment was rejection of the hypothesis that lignin biosynthesis is regulated on a transcriptional level, even though the lignin content was altered, as demonstrated by previous molecular characterizations. Thus, to connect lignification with pectin modification machinery, alternative hypothesis were tested and revealed a higher abundance of H2O2 and peroxidases in the PME over-expressing lines, compared to wild-type line, confirming a positive correlation between the lignin content, H2O2, and peroxidase activity. Furthermore, the up-regulation of a callose synthase gene in the xylem of one suppressed line; in addition to formation of tyloses, as a reaction of PME suppression, indicated a putative defense response. Many other genes involved in oxidative stress responses were observed significantly affected in transgenic lines. This unexpected result implicated activation of signaling cascades and signal transduction through critical stress pathways such as the salicylic acid, jasmonate and ethylene pathways. It might be speculated that the stress signaling was triggered by the elicitor oligogalacturonic acid (OGA), derived from the cell wall, as a result of its altered chemical composition, and that the lines may exhibit an increased pathogen/stress resistance.